Successfully reported this slideshow.
We use your LinkedIn profile and activity data to personalize ads and to show you more relevant ads. You can change your ad preferences anytime.

teori informasi

601 views

Published on

this article describes about information-theory for communication-channel

Published in: Education, Technology
  • Be the first to comment

teori informasi

  1. 1. Teori InformasiTeori Informasi Ir. Sihar, M.T. T. Informatika – Fak.Teknologi Informasi Bandung - 2012
  2. 2. Daftar PustakaDaftar Pustaka 1) Hartley, R.V.L. "Transmission of Information". Bell Labs Technical Journal. 1928. 2) Nyquist, H. "Certain Factors Affecting Telegraph Speed". Bell Labs Technical Journal. 1924. 3) Shannon, C. E. "A Mathematical Theory of Communication". Bell Labs Technical Journal. 1948.
  3. 3. Area dan domainArea dan domain Telegraph (th.1830) Telephone (th.1870) Wireless telegraph (th.1890) AM radio (th.1900) Single-Sideband-Modulation (1920) Television (th. 1930) Teletype (th.1930) Frequency Modulation (th.1930) PCM (th.1930) Vocoder (th.1930) Spread-spectrum (th.1930)
  4. 4. Skema sistem komunikasi Information source transmitter message signal noise source receiver destination message received signal Noise berasal dari lingkungan luar yang bersama-sama dengan sinyal data W= K log m W: speed of transmission data was transmitted K: Konstanta m: number of curret value was transmitted
  5. 5. W= K log m H: the amount of information a was transmitted S: number of possible symbols n: number of symbols in transmission H= log S n 12KB transmitted digital discrete H S n S n H
  6. 6. W= K log m H: the amount of information a was transmitted S: number of possible symbols n: number of symbols in transmission H= log S n 12KB transmitted digital discrete H S n S n H T RF(t)f 1 (t) f 2 (t)
  7. 7. Dalam Matematika Informasi menggunakan Shannon-Approach sbb: Engineering Mathematical Logic & Abstract Science
  8. 8. X + Y = Y + X X.Y = Y.X X + (Y + Z) = (X + Y) + Z X(Y.Z) = (X.Y)Z X(Y + Z) = X.Y + X.Z X + Y.Z = (X+Y)(X+Z) 1*X = X 0*X = 0 1+X = 1 0+X = X X + X’ = 1 X.X’ = 0 0’ = 1 1’ = 0 (X’)’ = X circuit terminal-A terminal-B XAB 0 1 ‘closed’ (zero-impedance) ‘opened’ (infinite-impedance)
  9. 9. Case and example:
  10. 10. Case and example:

×